Discovery of 6, 7-dihydro-5H-pyrrolo[3, 4-d] pyrimidine derivatives as a new class of ATR inhibitors. (1st May 2022) - Chen, Pei; Bin, Huachao; Jiao, Yan; Lin, Guifeng; Zhang, Yun; Xia, Anjie; Pan, Zhilin; Qiao, Jingxin; Guo, Yinping; Liu, Jingming; Zhou, Yangli; Li, Linli
Graphical abstract: Abstract: Ataxia telangiectasia and Rad3-related (ATR) kinase is a key regulating protein within the DNA damage response (DDR), responsible for sensing replication stress (RS), and has been considered as a potential target for cancer therapy. Herein, we report the discovery of a series of 6, 7-dihydro-5 H -pyrrolo[3, 4- d ]-pyrimidine derivatives as a new class of ATR inhibitors. Among them, compound 5g exhibits an IC50 value of 0.007 μM against ATR kinase. In vitro, 5g displays good anti-tumor activity and could significantly reduce the phosphorylation level of ATR and its downstream signaling protein. Overall, this study provides a promising lead compound for subsequent drug discovery targeting ATR kinase.